Hubungan Pola Makan Dan Self Image Dengan Status Gizi Remaja Putri SMA (15-18 Tahun) - Wahyuni Alinengsih; Veni Hadju; Aminuddin Aminuddin; Firdaus Hamid; Sharvianty Arifuddin; Burhanuddin Bahar (Poltekkes Kemenkes Bandung, 2020)
Objective: This study aims to study the relationship between eating patterns and self-image with nutritional status in high school girls (15-18 years) in Polongbangkeng Utara District, Takalar Regency. Method: A cross sectional study design with 170 students taken by purposive sampling technique in girls aged 15-18 years in SMA 6 and 11 in Polongbangkeng Utara Takalar Regency using questionnaires, anthropometry, and weighing levels of fat, in the month September-October 2019. This study uses analysis using the Chi Square Test. Results: The results of the analysis showed differences between adolescents' age, education age and retirement, adolescent nutritional status, results of statistical tests on diet with nutritional status based on BMI (p = 0.133> α = 0.05), self-image with nutritional status based on BMI (p = 0.86> α = 0.05), diet with nutritional status based on fat content (p = 0.333> α = 0.05), between self-image and nutritional status based on fat content (p = 0.869> α = 0.05), and between BMI with fat content (p = <0.001 <α = 0.05).